Some Malacological Journal Notes and Correspondence of E.S. Morse - Ralph W. Dexter (Hello World!, 1981)
Edward Sylvester Morse (1838-1925) was born and raised in Portland, Maine. As a boy he collected shells and minerals for a hobby; as a young man he was a draftsman, but in 1859 went to Harvard University to study under Louis Agassiz where he remained for three years. He was especially interested in mollusks and brachiopods. For a time he was curator of the Portland Society of Natural History, but in 1866 went to Salem, Mass., to become one of the founding curators at the Peabody Academy of Science. Between 1877-79 he went to Japan to conduct research on brachiopods and mollusks and to teach at the Imperial University of Tokyo. A second visit was made in 1882. He was the first president and one of the organizers of the Boston Malacological Club, founded in 1910. Below are selected excerpts from his journal entries and his correspondence which illustrate his concern with malacology.